Association of patterns of multimorbidity with length of stay: A multinational observational study. Issue 34 (21st August 2020) - Aubert, Carole E.; Schnipper, Jeffrey L.; Fankhauser, Niklaus; Marques-Vidal, Pedro; Stirnemann, Jérôme; Auerbach, Andrew D.; Zimlichman, Eyal; Kripalani, Sunil; Vasilevskis, Eduard E.; Robinson, Edmondo; Metlay, Joshua; Fletcher, Grant S.; et al.
Abstract : Abstract: The aim of this study was to identify the combinations of chronic comorbidities associated with length of stay (LOS) among multimorbid medical inpatients. Multinational retrospective cohort of 126, 828 medical inpatients with multimorbidity, defined as ≥2 chronic diseases (data collection: 2010–2011). We categorized the chronic diseases into comorbidities using the Clinical Classification Software. We described the 20 combinations of comorbidities with the strongest association with prolonged LOS, defined as longer than or equal to country-specific LOS, and reported the difference in median LOS for those combinations. We also assessed the association between the number of diseases or body systems involved and prolonged LOS. The strongest association with prolonged LOS (odds ratio [OR] 7.25, 95% confidence interval [CI] 6.64–7.91, P < 0.001) and the highest difference in median LOS (13 days, 95% CI 12.8–13.2, P < 0.001) were found for the combination of diseases of white blood cells and hematological malignancy. Other comorbidities found in the 20 top combinations had ORs between 2.37 and 3.65 (all with P < 0.001) and a difference in median LOS of 2 to 5 days (all with P < 0.001), and included mostly neurological disorders and chronic ulcer of skin. Prolonged LOS was associated with the number of chronic diseases and particularly with the number of body systems involved (≥7 body systems: OR 21.50, 95% CI 19.94–23.18, P < 0.001). LOS was strongly associated with specific combinations of comorbidities and particularly with the number of body systems involved. Describing patterns of multimorbidity associated with LOS may help hospitals anticipate resource utilization and judiciously allocate services to shorten LOS. Abstract : Supplemental Digital Content is available in the text